Pemanfaatan Susu Biji Durian Sebagai Pengganti Santan Dalam Pembuatan Bolu Kemojo Khas Riau - Ghini Kuntala Devi; Havifah Yolanda (Akademi Pariwisata NHI Bandung, 2026)
Bolu Kemojo is a traditional food specialty from Pekanbaru, Riau, which generally uses coconut milk as its main liquid ingredient. The high saturated fat content of coconut milk has prompted the search for healthier plant-based alternatives. On the other hand, durian seeds are an abundant consumption by-product (30–40% of the fruit's mass) but are rich in carbohydrates and starch. This study aims to examine the use of durian seed milk as a substitute for coconut milk in Bolu Kemojo in terms of taste, nutritional value, and shelf life. The method used was a true experimental design with organoleptic testing involving trained panelists (15 people) and untrained panelists (20 people) using a 1–5 Likert scale. Durian seed milk (1.11 g fat; 2.17 g protein per 100 g) has a much lower fat content than coconut milk (21 g saturated fat per 100 ml). The utilization of this by-product increases the economic value of local commodities while offering a lower-saturated-fat alternative for Bolu Kemojo Keywords: Bolu Kemojo, Durian Seed Milk, Coconut Milk Substitute, Experiment